Yi-Shen-Hua-Shi granules inhibit diabetic nephropathy by ameliorating podocyte injury induced by macrophage-derived exosomes - Liang, Mingzhu; Zhu, Xiaodong; Zhang, Di; He, Wenfang; Zhang, Jinshi; Yuan, Shizhu; He, Qiang; Jin, Juan (Frontiers in Pharmacology, 2022)
Objective: To observe the therapeutic effect of Yishen Huashi Granules (YSHS) in podocyte damage, diabetic nephropathy (DN) proteinuria and to explore the corresponding mechanism. Methods: The db/db mice were used to establish the diabetic neuropathy model. Serum creatinine, urea nitrogen and 24h urinary proteinuria were detected with specific kits. Glomerular structural lesions and glomerular cell apoptosis were detected through HE staining and TUNEL assay. The medicated Serum of YSHS (YSHS-Serum) or control serum was prepared. Macrophage-derived exosomes were extracted by exosome extraction kit. Morphology and the protein concentration of exosomes were evaluated by transmission electron microscope and BCA kit. The activity and apoptosis of podocyte MPC5 cells, the M1 macrophage polarization and the protein expression of exosome marker were detected by CCK-8 experiment, flow cytometry and Western blot respectively. The miR-21a-5p expression in podocytes and the exosomes from macropahge were measured by qRT-PCR. The effect of YSHS on the infiltration of M1 macrophages in the kidney tissue in db/db mice were measured by immunofluorescence. Results: YSHS could improve renal function, reduce proteinuria and inhibit glomerular structural lesions and glomerular cell apoptosis in db/db mice. High glucose stimulation and YSHS-Serum treatment did not affect the protein concentration in macrophage-derived exosomes. Macrophage-derived exosomes could inhibit the cell viability and increase apoptosis of podocytes, especially the exosomes from macrophage treated with high glucose and control serum. Compared with the exosomes secreted by macrophages after high glucose treatment, the exosome from macrophage treated with high glucose and YSHS-Serum showed lower inhibitory effects on podocyte activity, accompanied by the decreased up-regulating effects of macrophage-derived exosomes on the miR-21a-5p in podocytes. miR-21a-5p mimics could reduce podocyte activity and promote caspase 3 shearing. M1 polarization of macrophages could change the content of miR-21a-5p in macrophage-derived exosomes. In addition, YSHS-Serum could inhibit high glucose induced M1 polarization of macrophages and M1 macrophage infiltration in renal tissue. Conclusions: YSHS could improve the podocyte injury induced by macrophage-derived exosomes and alleviate the progression of diabetic nephropathy. This regulation might be related to the inhibition of M1 macrophage polarization by YSHS and the reduction of the miR-21a-5p content in macrophage-derived exosomes.